Use of Technology in Human Resource Management in the Digital Era "Case Study at the Class II Special Child Development Institution (LPKA) Palangka Raya" - Andriani; Rulandari, Novianita; Fitriyah, Aidatul (Politeia : Journal of Public Administration and Political Science and International Relations, 2025)
This study examines the implementation of technology in HRM at the Class II Special Child Development Institute (LPKA) Palangka Raya, focusing on its role in rehabilitating and developing children in conflict with the law. This research uses a qualitative descriptive approach to explore how LPKA Class II Palangka Raya navigates digital transformation while addressing institutional challenges. This study inidicate that technology enhances administrative efficiency, facilitates structured rehabilitation planning, and improves employee training programs. However, the institution faces significant challenges, including limited technological infrastructure, frequent staff rotations that disrupt program continuity, and financial constraints restricting access to advanced digital tools and training. Given these obstacles, this study underscores the need for strengthened technological infrastructure, enhanced digital literacy among staff and juveniles, and a more structured HRM strategy to optimize rehabilitation outcomes. By integrating appropriate technological solutions, LPKA Class II Palangka Raya can enhance the quality of rehabilitation programs, accelerate reintegration processes, and better equip juveniles for social reintegration. This research highlights the broader significance of digital adaptation in correctional institutions, emphasizing its potential to create more efficient and rehabilitative environments for juvenile offenders.